Chapter 14: Topical Preparations (A Text Book of Pharmaceutics for I Year Diploma in Pharmacy, 2024)
AuthorDr. Ghangale Gauri DhondibhauAssistant Professor, Amrutvahini College of Pharmacy, Sangamner, Maharashtra, IndiaAbstract: Topical preparations are dosage forms designed for application to the skin or mucous membranes, offering localized drug delivery and systemic effects in some cases. This section covers various types of topical formulations, including creams, ointments, gels, and transdermal patches. The structure and barrier properties of the skin are discussed in relation to drug penetration and absorption. Formulation considerations for topical preparations, such as drug solubility, partition coefficient, and vehicle selection, are explored to optimize drug delivery. The role of penetration enhancers and their mechanisms of action are examined. Manufacturing processes for different topical dosage forms are outlined, including emulsification techniques for creams and fusion method for ointments. Rheological properties of semi-solid preparations and their impact on drug release and application are addressed. Quality control tests specific to topical preparations, including viscosity, spreadability, and in vitro release studies, are detailed. Special considerations for sterile ophthalmic preparations and their packaging requirements are discussed.Keywords: Dermal delivery, Emulsions, Penetration enhancers, Rheology, Transdermal systems, BioavailabilityView PDF